An Aramaic graffiti from eastern Anatolia mentioning the tomb of an Artaxiad - Babur, Isa; Gorea, Maria (Semitica et Classica, 2023)
Abstract The writing of a graffiti carved into the wall of a rocky outcrop, situated not far from the course of the Araxe river in eastern Anatolia, belongs to the North-Mesopotamian branch of Aramaic. It mentions the name of one of the kings of the Artaxiad dynasty and possibly his grave. Abstract Le type d’écriture d’un graffite inscrit sur la paroi d’un alignement rocheux, situé non loin du cours de l’Araxe, en Anatolie de l’Est, se rattache à la branche nord-mésopotamienne de l’araméen. Le texte mentionne le nom de l’un des rois de la dynastie des Artaxiades et peut-être sa sépulture.